COVID-19 crisis responses through secondary database analysis: A comparison between Saudi Arabia and Indonesia - Yahya , Nasiha Hanis; Ambikapathy, Manimegalai (Jurnal Evolusi, 2023)
The COVID-19 pandemic has affected many people, be it individuals, family institutions, small businesses, government and non-governmental institutions, industrial sectors, health sectors, and many more. Despite the amount of pressure, different countries responded and reacted differently when it came to managing the issue. Governmental institutions and key players play a huge role in developing plans for each country’s continuity. Acknowledging that the pandemic has impacted the economic sector, especially those that revolve around businesses and global trade relations, hence the significance of this paper aims to compare the crisis responses between two affected countries when the COVID-19 pandemic hits mainly based on secondary data analysis. Considering the COVID-19 pandemic, responses by both countries Indonesia and Saudi Arabia have been listed to compare how they reacted, their action, and their plan for managing the pandemic. Can be depicted that both countries’ reactions and responses to this pandemic were subjected to resource availability and their economic background as well. Indonesia is the 4th most populous country in the world having a high poverty rate despite its growing economy, meanwhile, Saudi Arabia, is a rich country with wealth and a developed country with broad international relations with other countries, it can be concluded that Saudi Arabia’s response to the pandemic better than Indonesia. Overall, it can be concluded that despite anything, economic stability and citizens’ health are supposed to be the utmost priority in any country despite any political turmoil existing.